Practical Research and Optimization Strategy of ETC License Plate Recognition Supplementary Lighting Device - Zhu, Guanghu (Journal of Theory and Practice of Engineering Science, 2025)
With the rapid development of modern society and the continuous increase in traffic flow, the application of electronic toll collection systems (ETC) in highway toll stations is becoming increasingly common. In the ETC system, license plate recognition is a key link that can accurately and automatically identify the vehicle's license plate number, achieving fast toll collection. However, under certain specific conditions, such as at night or in low light conditions, it often affects the effectiveness of license plate recognition and brings certain difficulties to the operation of ETC systems.